Probability cueing of distractor locations: both intertrial facilitation and statistical learning mediate interference reduction - Goschy, Harriet; Bakos, Sarolta; Müller, Hermann J.; Zehetleitner, Michael (Frontiers in Psychology, 2014)
Targets in a visual search task are detected faster if they appear in a probable target region as compared to a less probable target region, an effect which has been termed “probability cueing.” The present study investigated whether probability cueing cannot only speed up target detection, but also minimize distraction by distractors in probable distractor regions as compared to distractors in less probable distractor regions. To this end, three visual search experiments with a salient, but task-irrelevant, distractor (“additional singleton”) were conducted. Experiment 1 demonstrated that observers can utilize uneven spatial distractor distributions to selectively reduce interference by distractors in frequent distractor regions as compared to distractors in rare distractor regions. Experiments 2 and 3 showed that intertrial facilitation, i.e., distractor position repetitions, and statistical learning (independent of distractor position repetitions) both contribute to the probability cueing effect for distractor locations. Taken together, the present results demonstrate that probability cueing of distractor locations has the potential to serve as a strong attentional cue for the shielding of likely distractor locations.